Private tertiary students’ unspoken thoughts in learning physical education amidst COVID-19 pandemic: Implications for intervention - CamariÃ±as, Rhealen P; Tagare, Ruben Lagunero (Edu Sportivo: Indonesian Journal of Physical Education, 2022)
COVID-19 Pandemic has impacted Higher Education worldwide, resulting in school closures to enforce social distancing protocols. Educational Institutions face profound changes in planning, implementing, and assessing their system, particularly in the Philippines. There is meager research on how COVID-19 influenced the educational system in the academic profession. As a result, this study utilized a Qualitative Phenomenology Research Design to explore further the information concerning private tertiary students' experiences learning physical education in the context of the COVID-19 Pandemic. Specifically, this study investigated the Private Tertiary Students’ lived experiences, coping mechanisms, and generated sensible suggestions to better implement the Tertiary Physical Education amidst the COVID-19 crisis. Using purposive sampling technique, 35 participants from private tertiary schools in the Cotabato Province in the Philippines took part in this qualitative research. Using open-ended questions as main instrument for the interviews, the necessary data were gathered and analyzed using the framework developed by Miles and Huberman - data reduction; data display; and conclusion drawing and verification. The findings of this study conclude that the lived experiences of private tertiary students were influenced by resource availability, support, and management, teaching and learning strategy, and student-teacher engagement. Improvements to facilities and equipment must be another focus of the school to increase students' learning experiences and boost their interest in physical education, which is essential for obtaining the desired performance rate and level of physical competence in the curriculum. Thus, this study implies that teachers should work conducive to professional growth and must interact with the learners and utilize adequate and efficient teaching strategies for the online learning of physical education. The findings were then used to develop conclusions and recommendations that can be used to improve and design interventions in online learning of physical education in the Philippine Private Tertiary schools.